Tabungan Wajib Pada Koperasi Ditinjau Dari HI - Tambunan, Salmia (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
A cooperative is a helping organization that carries out commercial business activities in a group based on the concept if helping. The purpose of this cooperative is to advance the welfare of this members in particular and society in general. The purpose of this research is to know how the mandatory savings application is cut by the mandiri jaya cooperative in sitataring, North padangsidimpuan district and how to review islamic law on mandatory savings in mandiri jaya cooperatives in sitataring, north padangsidimpuan. The type of research used in this research is fiel research, namely collecting data from customers and employees of the mandiri jaya Cooperative in Sitataring, North Padangsidimpuan District. Data collection techniques used are interviews and documentation. The results of research conducted at the Mandiri jaya cooperative in Sitataring, North Padangsidimpuan sub district, is mandatory savings at the Mandiri Jaya cooperative have been implemented properly because many customers complain that the customer’s saving are cut in half per savings by the cooperative and treat the savings contract as an advantage and provide benefits. Discount with a nominal that has been determined by the cooperative. The mandatory savings at the Mandiri Jaya cooperative in Sitataring, North Padangsidimpuan sub-district are not in accordance with Islamic law because the practice carried out by the cooperative is fraud. Mandiri Jaya cooperative in sitataring, North Padangsidimpuan sub-district is not to help each other but only to harm customers.